From the Cloud to the Edge: The Technical Characteristics and Application Scenarios of Fog Computing (International Journal of Automation and Smart Technology, 2025)
International Telecommunication Union clearly defines IoT (Internet of Things) as “a phenomenon where every standalone object is connected”, this shows that as connectivity and communications technology gradually mature, various linking devices and equipment will be able to connect and create a more rich and diverse service scenario. However, as this trend is being established, these connected devices will produce large amount of data, which in turn will cause two problems that need to be solved: first, the increasing number of connected devices will lead to data congestion. The current solution is to process data in batches to divert data flow, but this will still result in latency and inability to respond to the issue immediately; second, with the advent of more wireless and cable-connected devices, service operators will have to invest more into the installation of cloud infrastructure. Aside from the initial installation, follow-up maintenance will also require huge costs, bumping up service prices. In response to the problems with the IoT, the structure of edge computing called “fog computing” was created. It can be defined as “an emerging method of computing with the main goal of shifting computing and connecting units from the cloud to the edge or nearedge position to help devices preemptively and autonomously process information and data created by connected devices, creating a computing structure that can operate without relying on the center.